Calcium Signals during SARS-CoV-2 Infection: Assessing the Potential of Emerging Therapies - Sascha Berlansky; Matthias Sallinger; Herwig Grabmayr; Christina Humer; Andreas Bernhard; Marc Fahrner; Irene Frischauf (Cells, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a positive-sense single-stranded RNA virus that causes coronavirus disease 2019 (COVID-19). This respiratory illness was declared a pandemic by the world health organization (WHO) in March 2020, just a few weeks after being described for the first time. Since then, global research effort has considerably increased humanity’s knowledge about both viruses and disease. It has also spawned several vaccines that have proven to be key tools in attenuating the spread of the pandemic and severity of COVID-19. However, with vaccine-related skepticism being on the rise, as well as breakthrough infections in the vaccinated population and the threat of a complete immune escape variant, alternative strategies in the fight against SARS-CoV-2 are urgently required. Calcium signals have long been known to play an essential role in infection with diverse viruses and thus constitute a promising avenue for further research on therapeutic strategies. In this review, we introduce the pivotal role of calcium signaling in viral infection cascades. Based on this, we discuss prospective calcium-related treatment targets and strategies for the cure of COVID-19 that exploit viral dependence on calcium signals.